(untitled) (Global Journal of Management and Business Research, 2019)
The main purpose of this paper is to examine the perception of accounting experts on the implementation of integrated reporting in Sri Lanka. Integrated reporting provides a wide range of information especially financial and non-financial information to economic decision makers of the company. Primary data used in this study which was collected from accounting experts such as academician, auditors, professional accountants/ chief financial officer, accounting special degree graduated students, undergraduate students and accounting related professional studies students in Sri Lanka. Primary data collected through a 5 points Likert scale questionnaire. Questionnaire of this study covers two major parts, opportunities and benefits, challenges and disadvantages on the implementation of integrated reporting. Descriptive analysis performed in this study with the help of SPSS latest version. Mean analysis confirmed that opportunities and benefits on the implementation of integrated reporting are more than challenges and disadvantages on the implementation of integrated reporting in Sri Lanka. Further, this study found that there is a lack of knowledge and awareness regarding integrated reporting in Sri Lanka. Respondents of this study strongly recommended that there should be needed proper training program on integrated reporting for internal and external stake holders of the company.